Intraneural Synovial Sarcoma of the Median Nerve in a 15-Year-Old Male: A Case Report and Review of Literature. (March 2022) - Samia, Arthur; Scarcella, Joshua; Zeri, Richard; Guo, Yifan
There have been 8 synovial sarcomas of the median nerve reported. We report a case of a 15-year-old male with synovial sarcoma of the right-hand median nerve. Patient presented with a 2-month history of enlarging mass at the base of the right thenar eminence associated with numbness in the median nerve distribution. Physical examination revealed a soft mass over the thenar eminence and paresthesia in the median nerve distribution. He underwent excision of the tumor, which revealed a well-encapsulated lesion encompassing the median nerve, involving the first, second, and radial aspect of the third web space as well as recurrent branches of the median nerve. Following excision of the tumor, a thorough metastatic workup was negative for metastatic disease. He was staged as III, T2b, N0, M0—poorly differentiated monophasic synovial sarcoma of the right median nerve. Postoperatively the patient was started on chemotherapy and radiation. Intraneural synovial sarcoma is extremely rare. Our case is the youngest with the longest follow-up. He is currently at a status of 3 years posttreatment with no signs of recurrence and excellent use of his right hand. This case is of particular interest due to the rarity of the disease along with this being the best outcome reported in the literature to-date.